Peran Pendidikan Agama Islam Berwawasan Multikultural Dalam Meningkatkan Indeks Religiusitas Di SMK Muhammadiyah 1 Taman: Peran Pendidikan Agama Islam Berwawasan Multikultural Dalam Meningkatkan Indeks Religiusitas Di SMK Muhammadiyah 1 Taman - Jasmine Aziz; Rahmad Salahuddin Tri Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of Islamic Religious Education (IRE) with a multicultural perspective in improving the religiosity index of students at SMK Muhammadiyah 1 Taman. Using a descriptive qualitative approach, data were collected through interviews, observations, and document studies involving students, teachers, and the school principal. The findings reveal that religiosity is reflected not only in ritual worship practices, such as prayer, fasting, and Qur’an recitation, but also in social attitudes such as tolerance, mutual respect, and adherence to rules. The integration of multicultural values in IRE, supported by teacher modeling, routine religious programs, and classroom agreements, significantly strengthens students’ religiosity. The average score of 8.7 out of 10 indicates that students achieved a high level of religiosity. However, challenges remain, including the influence of social media, inconsistent behavior outside school, and diverse family backgrounds. The study concludes that multicultural IRE fosters both religious commitment and social harmony.